Analysis of in-vitro reaction layers formed on plasma sprayed bioglass-titanium coatings - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
Bioglass, 45S5 containing 45% SiO2, 6% P2O5, 24.5%, CaO and 24.5% Na2O all in weight percent, was plasma sprayed onto a titanium substrate with and without 60Al(2)O(3) 40TiO(2) as a bond coating. It has been observed that there is a uniform coating layer with a thickness of 110 mum and that there was not any reaction observed at the coating-metal interface for both coating application. In vitro assessment of bio-activity was carried out by immersing in Simulated Body Fluid (SBF). Fourier transform infrared spectroscopy and thin film X-ray diffraction techniques were used to analyze the inorganic carbonate apatite layer developed on coating in an in-vitro environment. Scanning electron microscopy was used to surface characterization.
Keywords: bioglass; simulated body fluid; BEHAVIOR